PROSPECTIVE SCENARIOS OF HIGHER EDUCATION TO 2030: CASE OF THE CHIMBORA-ZO POLYTECHNIC HIGHER SCHOOL - Salinas Marín, Marcela; Vásquez Criollo, Alexander; Rodríguez Ulcuango, Olga; Saltos Aguilar, Wilson Manuel (mktDESCUBRE; Vol 1 No 2 (2020): Special Edition 3rd International Scientific Congress of Administrative and Financial Sciences FADE 2019DO - 10.36779/mktdescubre/v#.#, 2020)
This article proposes the generation of prospective scenarios of Higher Education by 2030, based on the case of a study by the Polytechnic School of Chimborazo, with the purpose of proposing a quality education system based on the latent needs of society, for this way to be a national and international reference. The study methodology promotes a strategic prospective analysis, which consists of idealizing the future, taking into account the opinion of key actors, who helped in the construction of possible scenarios, through the use of several tools such as: prospective workshops, analysis MICMAC structural and morphological analysis (MORPHOL method). Technology constantly advances by leaps and bounds as well as study methodologies and social problems, so it is crucial to carry out a prospective study that helps to have a vision about how to deal with these changes, because of the above and according to the results obtained in which the shortcomings of the current educational system were evidenced, the construction of a negative, positive and trend scenario has been carried out that will help to structure an educational system based on the generation and transfer of knowledge.